Influence of legal barriers and limitation of water resources, as a competitive factor for the export of Solanum lycopersicum - Linares-Vizcarra, Mitzi Lourdes del Carmen (2022)
In Peru, biodiversity enables the variety of vegetables in the regions, making viable agricultural trade abroad. Currently, there are legal barriers that have a negative influence on the competitiveness of Solanum lycopersicum exports. The study raises the negativity of the tariff barriers for the economic growth of Peru. The study method is qualitative. It worked with 26 exporting organizations, using questionnaires and secondary sources to obtain data, being a basic investigation of correlational level and transactional-descriptive design. Foreign direct investment in Peru is one of the most notable; however, it can be diversified according to the risk factor country, under the different political scenarios experienced by the countries with commercial relations. It is considered that 85.71 % of the agro-industrial exporters of Tacna process these products, 14.29 % admit not to process agro-industrial products; 57.14 % of the respondents indicate that the legal factor presents legal barriers, because 64.29 % of the respondents think that the legal structure of Peru is detrimental to exports, especially for Tacna. The variation of the existing legislation limits the planting of products destined for agro-export in Tacna, considering that it is a city that is in a desert area, for this reason 82.14 % believe that crop planning is necessary, due to the insufficiency of the resource hydric